PERSEPSI DAN KESIAPAN SISWI SD DALAM MENGHADAPI MENARCHE - Suzahra Khoirunisya; Suryanti, Suryanti (Medical Journal of Nusantara, 2024)
Menarche is the first menstruation due to the shedding of the lining of the uterus (endeometrium) in the uterus. This is accompanied by various changes, both physical and psychological. These changes can be accepted by the child or rejected by the child. In order for these changes to be well received, female students' perception and readiness regarding the monarchy is needed. This research aims to determine the perceptions and readiness of elementary school students in facing menarche. The research method uses Quasi Experimental with a two group pre-post test design. The sampling technique is total sampling using video and booklet media. Research results: education with booklets increased students' positive perceptions about the monarchy, namely from 43.5% to 60.9% and increased female students' readiness in facing the monarchy from 78.3% to 89.6%. Meanwhile, video increases student perception from 60.9% to 78.3 and readiness from 65.2% to 91.3%. The Wilcoxon test results obtained a significance value of 0.000 or <0.05. Conclusion: Education using booklets and video media has an influence on perceptions and readiness of elementary school students in facing menarche